STUDY ON ADAPTIVE CAPACITY AND BEHAVIORAL STRESS OF SEPARATION (MOTHER-JUVENILE) IN RATS WISTAR (Sciences & Technologie. C, Biotechnologies, 2013)
In humans, genetic and environmental factors influence susceptibility to many diseases. In particular, the quality of relationships between a child and his mother plays an important role for the harmonious development and the subsequent equilibrium of this individual. Perturbations of these relationships can lead to such serious psychiatric disorders. More, experimental animal models are developed in order to know the neurobiological disturbances that underlie vulnerability to these disorders. Modeling animal remains relative. The work presented in this paper was carried out on a model of mother / newborn rats (Tusrattus) of the Wistar strain separation. The rats are separated from their mothers and isolated from conspecifics daily for 5 min, 30 min and an hour of their third to their 14th day of life. Studies have already been conducted in this model, in rats became adults. It was this time to analyze the behavior of rats at the age juvénile. The first part presents the general context within forms the subject, and includes bibliographic data models . The second part presents the specific objectives of the work. It will be followed by a third part describes the experimental work. Different behavioral realized tests will be explained, and then the results explain that the longer duration of separation increases behavioral responses, compared to those in the literature.